2018
DOI: 10.1016/j.bmc.2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and profiling of benzylmorpholine 1,2,4,5-tetraoxane analogue N205: Towards tetraoxane scaffolds with potential for single dose cure of malaria

Abstract: A series of aryl carboxamide and benzylamino dispiro 1,2,4,5-tetraoxane analogues have been designed and synthesized in a short synthetic sequence from readily available starting materials. From this series of endoperoxides, molecules with in vitro IC50s versus Plasmodium falciparum (3D7) as low as 0.84 nM were identified. Based on an assessment of blood stability and in vitro microsomal stability, N205 (10a) was selected for rodent pharmacokinetic and in vivo antimalarial efficacy studies in the mouse Plasmod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…2, αmono-substituted, αdisubstituted, and αtrisubstituted aliphatic amines were smoothly converted. Briefly, aliphatic amines bearing alkyl and alkoxyl groups (41 to 52), Boc-and benzyl (Bn-) protected amines (53 to 64), ester (65), alcohol (66 to 67), sulfide (68), sulfone (69), and trifluoromethyl (70) groups all underwent the desired transformation to afford the products smoothly. And no erosion was observed when stereocenters were presented (54, 56 to 58, 64 to 66, and 70).…”
Section: Resultsmentioning
confidence: 99%
“…2, αmono-substituted, αdisubstituted, and αtrisubstituted aliphatic amines were smoothly converted. Briefly, aliphatic amines bearing alkyl and alkoxyl groups (41 to 52), Boc-and benzyl (Bn-) protected amines (53 to 64), ester (65), alcohol (66 to 67), sulfide (68), sulfone (69), and trifluoromethyl (70) groups all underwent the desired transformation to afford the products smoothly. And no erosion was observed when stereocenters were presented (54, 56 to 58, 64 to 66, and 70).…”
Section: Resultsmentioning
confidence: 99%
“…The finding that N205 178b had the same effectiveness as four times the amount of artesunate 4b suggested a solo dosage of N205 had comparable effectiveness with the multiples of artesunate 4b when given orally (Figure 39). 260 …”
Section: Some Antimalarial Endoperoxide Moieties Other Than 124‐triox...mentioning
confidence: 99%
“…In docking conformations performed by the same group, they have found that the shortest distance was between heme Fe(II) assay. 136 Looking forward, the incorporation of synthetic endoperoxide antimalarials into ACT regimens might be the solution to the looming threat of ART resistance.…”
Section: E209mentioning
confidence: 99%